(untitled) (Indian Journal of Animal Production and Management, 2024)
The working equines are important species in India especially for the marginalised, socio economically weaker sections of society. Recent years have witnessed a decline in their population due to various reasons. Numerous work types of working equids including mules, donkeys and horses are found in different states as per work requirement, climate and geography The animals of these species face varied welfare problems. Non availability of adequate recourses, lack of knowledge and skills of rearing communities, metabolic and other diseases are the major welfare problems encountered by these animals. This paper discusses the welfare problems faced by the working equines in India and suggests a methodology for the assessment of welfare of these animals. This paper also offers a detailed strategy and actin plan for the improvement of welfare of these animals in India.